(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The article based on comparative study of national cultural peculiarities of speech etiquette in the English and Uzbek languages. The study deals with the similarities and distinctive features of the topic of conversation, addressing, greeting expressions . Instances provided both languages.